Intradural Extramedullary Spinal Ependymoma: A Case Report of Malignant Transformation Occurring - Moriwaki, Takashi (Korean Society of Spine Surgery, 2013)
Intradural extramedullary spinal ependymomas are extremely rare. Herein, we describe a lesion-type spinal ependymoma that followed a malignant course, and discuss its clinical presentation, etiopathogenesis, and treatment. We present a patient who was diagnosed with an intradural extramedullary spinal tumor at T4-T6. The patient underwent gross total resection of the tumor without damage to the spinal cord. Histological examination, classified the lesion as a World Health Organization (WHO)-grade 2 ependymoma. One and a half years later, magnetic resonance imaging detected a recurring tumor at T4-T5. The tumor was removed and classified as a WHO-grade 3 anaplastic ependymoma. The patient was started on a course of regional spinal cord radiotherapy. The patient achieved tumoral control and clinical stabilization after the recurrence. We must consider the differential diagnosis of intradural extramedullary spinal tumors. The best treatment for this lesion is gross total resection and adjunctive radiotherapy is necessary in cases of malignant-change.